2013
DOI: 10.1158/0008-5472.can-12-1321
|View full text |Cite
|
Sign up to set email alerts
|

Bcl3 Selectively Promotes Metastasis of ERBB2-Driven Mammary Tumors

Abstract: Bcl3 is a putative proto-oncogene deregulated in hematopoietic and solid tumors. Studies in cell lines suggest that its oncogenic effects are mediated through the induction of proliferation and inhibition of cell death, yet its role in endogenous solid tumors has not been established. Here, we address the oncogenic effect of Bcl3 in vivo and describe how this Stat3-responsive oncogene promotes metastasis of ErbB2-positive mammary tumors without affecting primary tumor growth or normal mammary function. Deletio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 53 publications
5
62
0
Order By: Relevance
“…The immunohistochemical analysis of BCL3 protein revealed statistically significant higher expression levels in neoplastic tissues compared to tumor-adjacent, normal lung specimens where no signal was detected. This finding is consistent with published data reporting deregulation of BCL3 expression in other solid tumors such as breast cancer [12][13][14][15], prostate cancer [16], nasopharygeal carcinomas [17], endometrial tumors [18] and colorectal cancer [19]. The overexpression of BCL3 in all histological subtypes and all stages of NSCLC may reflect the decisive role that this molecule plays in lung carcinogenesis and tumor progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The immunohistochemical analysis of BCL3 protein revealed statistically significant higher expression levels in neoplastic tissues compared to tumor-adjacent, normal lung specimens where no signal was detected. This finding is consistent with published data reporting deregulation of BCL3 expression in other solid tumors such as breast cancer [12][13][14][15], prostate cancer [16], nasopharygeal carcinomas [17], endometrial tumors [18] and colorectal cancer [19]. The overexpression of BCL3 in all histological subtypes and all stages of NSCLC may reflect the decisive role that this molecule plays in lung carcinogenesis and tumor progression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, BCL3 has been documented to be deregulated in a number of solid tumors including breast cancer [12][13][14][15], prostate cancer [16], nasopharygeal carcinomas [17], endometrial tumors [18] and colorectal cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have been reported using the NIC mice and none have observed haplo-insufficiency for genes required for Neu-induced mammary tumorigenesis. Genes examined for their role in ERBB2-mediated mammary tumorigenesis include ShcA [32], β-catenin [42], Bcl3 [43], hexokinase II [44], DOCK1 [45], LKB1 [46], 14-3-3σ [47], STAT1 [48], and specific isoforms of phosphatidylinositol 3’-kinase [49]. The haplo-insufficiency observed in our study indicates a strong requirement for GLUT1 and glucose in mammary tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Bcl3 expression results in increased cell proliferation, survival and malignant potential. Studies have demonstrated increased Bcl3 expression in the different types of hematopoietic and solid cancers [4449], yet its function and regulation in CTCL have not been investigated.…”
Section: Introductionmentioning
confidence: 99%